1988
DOI: 10.1152/ajpendo.1988.255.3.e236
|View full text |Cite
|
Sign up to set email alerts
|

Very-low-density lipoprotein triglyceride kinetics in acute and chronic carbohydrate-fed rats

Abstract: Very-low-density lipoprotein (VLDL)-triglyceride (TG) kinetics were examined in rats maintained on either chow and water (control) or chow and a 10% carbohydrate drinking solution (fructose or glucose). The hexose solutions were available for an acute (16 h) or chronic (14 day) period. The acute fructose (AF), acute glucose (AG), and chronic fructose (CF) groups were hypertriglyceridemic (HTG) compared with control. Plasma TG concentration in chronic glucose (CG)-fed rats was similar to control. VLDL-TG was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…Fructose feeding causes overproduction of TG in the liver (25) and a defect in TG catabolism due to altered composition and nature of very-low-density lipoprotein particles (26). Olmesartan remarkably suppressed TGSR without affecting LPL concentration in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose feeding causes overproduction of TG in the liver (25) and a defect in TG catabolism due to altered composition and nature of very-low-density lipoprotein particles (26). Olmesartan remarkably suppressed TGSR without affecting LPL concentration in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most published studies in rats or mice did not show an inhibitory effect of thiazolidinediones on VLDL secretion, thereby concluding that the lowering of plasma TG resulted in total or in part from increased VLDL clearance (22,24,25). Unlike the fructose-fed hamster and insulin resistant humans, the rodent models used in the latter studies display impaired plasma TG clearance as the major mechanism of their hypertriglyceridemia when they become insulin-resistant (8). This perhaps explains the discrepancy between our results and those of the latter studies.…”
Section: Discussionmentioning
confidence: 99%
“…These animal models may not, however, be ideal for the study of human lipoprotein disorders because, unlike humans, their livers secrete both apoB48 and apoB100-containing VLDL, and they do not necessarily develop VLDL oversecretion as the basis for their hypertriglyceridemia (8,9). Unlike livers from rat or mouse, the liver of the golden Syrian hamster secretes only apoB100-containing VLDL, and its lipoprotein metabolism more closely resembles that of humans (10).…”
mentioning
confidence: 99%
“…TG secretion rate (TGSR) in vivo may also be determined by injecting radiolabeled VLDL-TG, or a precursor of TG such as glycerol , and determining the turnover rate of VLDL-TG under steady-state conditions (4-6) . There have been several reports (7)(8)(9), including work from our laboratory (10) , that have indicated that calculated TGSR may differ substantially depending on which method is employed. Few studies have examined the relationship of TGSR derived by the tracer or the triton methods .…”
Section: Discussionmentioning
confidence: 99%